Vibrational Spectrum of Magnesium Monochalcogenide Nanoparticles - Nikos Aravantinos-Zafiris; Fotios I. Michos; Michail M. Sigalas (Nanomaterials)
In this work, the vibrational spectra of magnesium monochalcogenide nanoparticles were examined numerically. The calculations were performed with Density Functional Theory and the examined magnesium monochalcogenide nanoparticles were formed from an initial cubic-like unit with type <semantics>Mg4Y4</semantics>, where <semantics>Y=S,Se,Te</semantics>, after elongating this unit along one, two, and three vertical directions. Therefore, beyond the initial building block, different groups of magnesium monochalcogenide nanoparticles were examined in the form <semantics>MgxYx</semantics>, where <semantics>x=8,16,24</semantics>. Especially for the case where the chalcogen part of the nanoparticle was sulfur, another group of nanoparticles was examined where <semantics>x=32</semantics>. For this group of the examined nanostructures, an exotic case was also included in the calculations. Among the findings of this research was the existence of stable structures, of the examined morphologies. The calculations of this research led to the identification of both common characteristics and differences among these nanostructures. These characteristics regarding their vibrational modes could be a very useful tool, especially for experimentalists. The relevant phonon spectrum that was extracted from the calculations also provided very useful information regarding the examined nanoparticles and their potential uses in several technological applications.